The Development Model of Medical Missionary Work: From Shengjing Hospital to Fengtian Medical University (1883–1912) - WU Zhihua, (Journal of Research for Christianity in China (JRCC), 2025)
In 1883, Scottish Presbyterian missionary Dougald Christie established a Western medicine clinic motivated by missionary work, which evolved into Shengjing Charity Hospital by 1887. Shengjing Western Medical School was founded in 1892 as an affiliate of Shengjing Charity Hospital. When the Shengjing Medical School evolved into Fengtian Medical University in 1912—the first modern medical university in Northeast China—the Shengjing Shi Hospital became its teaching and affiliated hospital. This reversal in the relationship between school and hospital exemplified the developmental pattern of medical missionary work: progressing from clinics (hospitals) to Western medical schools (medical universities). This evolution stemmed from the missionaries' own motivations and ideological development, the Chinese government and society's high recognition and urgent need for Christianity and Western medicine in particular, as well as the Shengjing Charity Hospital's own developmental requirements and outcomes.
Keywords: Presbyterian Church, Fengtian Medical University, Medical Missionary